A Collective-Distributive Pragmatic Scale and the Developing Lexicon. Issue 1 (2nd January 2021) - Grinstead, John; Padilla-Reyes, Ramón; Nieves-Rivera, Melissa
ABSTRACT: A locus of the difference in meaning between distributive and collective sentences can be the quantifiers that modify their subjects. A current theoretical account of distributive and collective sentences claims that sentences with quantifiers such as the in English, or los in Spanish, in subject position and an indefinite direct object, modified by a in English, or una in Spanish, are ambiguous as to whether they are distributive or collective, all things being equal. In contrast, the same sentences with each/cada in subject position are unambiguously distributive. This account claims that sentences with quantifiers such as the/los in subject position come to be interpreted collectively, and not distributively, because the distributive meaning could more informatively be constructed using the unambiguous each/cada quantifier. This is the same neo-Gricean reasoning that accounts for the Quantity Implicature that arises for some, given the informativeness of all . On this account, collective and distributive interpretations are intrinsically linked, which predicts that even children's non-adult-like collective and distributive interpretations should nonetheless be statistically associated, which we confirm in a sample of Puerto Rican Spanish-speaking children. We further propose that growth occurs both internal to lexical items, in terms of denotative content, as well as externally, within the lexicon in quantifier networks. Such networks have traditionally been expressed in formal semantics as pragmatic scales. We claim that the growth of both of these lexical dimensions are indexed by general lexical growth and show that a statistical association obtains between them in our sample.